Morus Tamás Utópiájának magyar fordításai - Czigányik, Zsolt (Studia Litteraria, 2024)
The first Hungarian translation of omas More’s Utopia by Ferenc Kelen was published rather belatedly in 1910, followed by an abridged translation in 1941, by László Geréb. Two years later a new, precise but modern translation was prepared by Tibor Kardos. A shorter selection of More’s original was also published in the fifties in András Bodor’s translation. Until the 1963 edition of Kardos’s translation, Utopia was presented as an important text in social philosophy, with detailed introductions, afterwords, and notes to the text. Recent editions usually place the emphasis on the literary qualities of the text. All the translations are based on the Latin version, usually the 1518 Frobenius (Basel) edition or Michels and Ziegler’s 1895 critical edition. The presence of the paratexts varies in the different translations: More’s letter to Giles is usually translated, yet most of the other parerga are ignored. Recent editions are usually illustrated, with the illustrations often (but not always) based on the 1518 Frobenius edition. The absence of a Hungarian translation in the first four centuries after the first publication of More’s Utopia is counterweighted by not fewer than eleven editions in the twentieth and twenty-first centuries.